2018
DOI: 10.1073/pnas.1713837115
|View full text |Cite|
|
Sign up to set email alerts
|

High salt intake causes leptin resistance and obesity in mice by stimulating endogenous fructose production and metabolism

Abstract: Dietary guidelines for obesity typically focus on three food groups (carbohydrates, fat, and protein) and caloric restriction. Intake of noncaloric nutrients, such as salt, are rarely discussed. However, recently high salt intake has been reported to predict the development of obesity and insulin resistance. The mechanism for this effect is unknown. Here we show that high intake of salt activates the aldose reductase-fructokinase pathway in the liver and hypothalamus, leading to endogenous fructose production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
220
6
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(248 citation statements)
references
References 33 publications
5
220
6
4
Order By: Relevance
“…Other potential mechanisms include effects on vasopressin or by stimulating endogenous cardiotonic steroids such as ouabain and marinobufagenin . High salt_induced osmolality may also stimulate the aldose reductase_fructokinase pathway in the hypothalamus that might mediate blood pressure responses . Thus, salt_induced hyperosmolarity may be involved in both classical renal and central nervous system blood pressure control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms include effects on vasopressin or by stimulating endogenous cardiotonic steroids such as ouabain and marinobufagenin . High salt_induced osmolality may also stimulate the aldose reductase_fructokinase pathway in the hypothalamus that might mediate blood pressure responses . Thus, salt_induced hyperosmolarity may be involved in both classical renal and central nervous system blood pressure control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…). In turn, aldose reductase can be stimulated by high glucose levels (such as in diabetes), by high‐salt diets (which increases osmolality, a known stimulant of aldose reductase), heat, tissue hypoxia, oxidative stress and by fructose and uric acid . In western societies, the main sources of fructose are from table sugar (sucrose) and the sweetener, high‐fructose corn syrup (HFCS).…”
Section: Fructose As a Survival Factormentioning
confidence: 99%
“…A high serum osmolality, such as occur in dehydration or high‐salt intake, has been found to stimulate endogenous fructose pathway through the activation of aldose reductase. In this regard, blood pressure rise can be prevented in hyperosmolar animals lacking fructokinase . High‐salt intake also interacts with dietary fructose to raise blood pressure .…”
Section: Fructose Maintains Blood Pressure By Retaining Sodium and Efmentioning
confidence: 99%
“…HSD could be an independent factor in promoting gastric carcinogenesis. Emerging studies have shown that HSD is associated with diseases other than GC, such as hypertension, obesity, diabetes, fatty liver, neurovascular, and cognition dysfunction . Furthermore, HSD is closely associated with an altered Th17 response in the disease process .…”
Section: Environmental Factors Are Associated With Gc Riskmentioning
confidence: 99%
“…Emerging studies have shown that HSD is associated with diseases other than GC, such as hypertension, obesity, diabetes, fatty liver, neurovascular, and cognition dysfunction. [72][73][74] Furthermore, HSD is closely associated with an altered Th17 response in the disease process. 72,74,75 However, the precise mechanism through which HSD interacts with the host and bacteria to promote gastric carcinogenesis remains to be elucidated.…”
Section: Dietary Factors Are Associated With Gc Riskmentioning
confidence: 99%